Multiple clear cell acanthomas and a sebaceous lymphadenoma presenting in a patient with Cowden syndrome – a case report. (20th October 2016) - Potenziani, Silvia; Applebaum, Danielle; Krishnan, Bhuvaneswari; Gutiérrez, Carolina; Diwan, A. Hafeez
Abstract : Cowden syndrome (CS) is an uncommon autosomal dominant multiorgan/system genodermatosis. It is characterized by the development of multiple hamartomas of endodermal, mesodermal and ectodermal origin, an increased lifetime risk of breast, thyroid, endometrial and other cancers and an identifiable germline mutation. Mucocutaneous hamartomas are the most common lesions seen and mainly include facial trichilemmomas, oral mucosal papillomas and benign acral keratoses. Herein, we report a case of a 63‐year‐old Caucasian male with a long‐established diagnosis of CS and history of thyroid cancer, colonic polyps, and innumerable trichilemmomas, seborrheic keratoses, squamous papillomas and non‐melanoma skin cancers excised in the past. He presented in four separate occasions with small skin‐colored papulonodular lesions that upon excision revealed to be clear cell acanthomas. He also developed a tumor in the preauricular area that was completely resected and was found to be a sebaceous lymphadenoma (SLA) of the parotid gland. This is to our knowledge, the second report of clear cell acanthoma and also the second reported case of SLA in a patient with CS.